ANAGLYPH AND 3D MODEL USAGE IN EDUCATION OF MECHANICAL ENGINEERS - Zorana Jeli; Branislav Popkonstantinovic; Misa Stojicevic; Ljubomir Miladinovic (Journal of Industrial Design and Engineering Graphics, 2017)
The development of computer technology and the use of 3D software has led to substantial changes in the education system and the way of thinking for future engineers. Until recently, both engineers and future engineers had to use plane projection for a spatial view of a certain part, making orthogonal design a necessity. However, due to advanced technology development, especially in the field of computers, this is no longer necessary. This paper provides an overview of the ideas that have been implemented in several courses held at the Faculty of Mechanical Engineering in Belgrade, where future engineers have the ability to learn about simpler, more modern and more efficient ways in which they can deal with the design of technical systems. The use of 3D modelling software packages in the design process significantly reduces the necessary time, and certain analyses of technical systems are made simpler and more accurate. For easier understanding of the problems of spatial layout and functionality of technical systems, students are learning about easy ways to display a physical technical system. This paper gives ideas on how to develop the education system for future mechanical engineers, but also how to prepare them to understand the traditional way of engineering and the design of technical systems.